Comparison on the efficacy of analgesia using Transversus Abdominis Plane (TAP) block and Intravenous Diclofenac after caesarean delivery under spinal anaesthesia (Journal of Dhaka National Medical College & Hospital, 2024)
Background: The Transversus Abdominis Plane(TAP) block is a regional field block that provides effective analgesia after lower abdominal surgeries as postoperative analgesia is a major component of perioperative care.Objective: To evaluate the effectiveness of intravenous Diclofenac and Ttransversus Abdominis Plane (TAP) block analgesia following caesarean delivery (LUCS) under spinal anesthesia (SAB).Methods: In this prospective, observational study, 40 healthy participants who underwent LUCS under SAB were included. Group A (n = 20) received a bilateral TAP block with Bupivacaine 0.5% (1.5 mg/kg), while Group B (n = 20) were given intravenous diclofenac sodium. Adverse consequences, the overall length of postoperative analgesia, pain rating scale scores, and patient satisfaction levels were also documented. P value less than 0.05 was considered to be significant. Results: In comparison to Group B (8.20-0.90 h), Group A's total analgesic duration was longer (16.30+1.16 h) it was statistically highly significant. The total amount of analgesics needed in the first 24 hours after surgery was lower in Group A (104.19+28.3 mg) than that of Group B (165.14+32.6 mg) which was statistically significant. Mean pain rating scale scores in Group A were significantly lower than those of Group B at 6, 12 and 24 post-operative hours. Patients in Group A also reported higher levels of satisfaction than those of Group B, the difference was statistically highly significant.Conclusion: Compared to intravenous diclofenac sodium, bilateral TAP block Bupivacaine following LUCS under SAB offers superior post-operative analgesia and better patient satisfactionJ. Dhaka National Med. Coll. Hos. 2024; 30 (01): 38-41